ANALISIS PENGELOLAAN KEUANGAN USAHA BERBASIS ELEKTRONIK PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Irawan, Riya; Witarsa, Witarsa; Budiman, Jumardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to determine the electronic-based business financial managemen of FKIP UNTAN economics studenst. To analyze the business financial management process, several, aspects are needed, namely planning, recording, controlling, and reporting. The research method used is descriptive with a qualitative case study form. The data source for this research is students who are online shop business actors from 2016 to 2019 and the data is the result of interviews with economics education students. The result of the study show that all research informations who become online shop business actors have managed their finances, for the continuity of the informants business leads to the fulfillment of business information carried out in accordance with the needs ans abilities of each informant. In electronic-based business financial management, students use social media as a substitute for physical stores to promote sales, carry out financial planning on a monthly basis, keep financial records for each sales transaction, carry out financial control according to their respective experiences and for financial reporting only by looking at record recapitulation only and 1 informant made a profit and loss report. This financial management has a direct influence on the running of a business because it can optimize business finances efficiently and also contains information that makes it easy to make decisions to achieve business goals.